Dormancy Breaking in Ormosia arborea Seeds - Edilma Pereira Gonçalves; Franklim Sales de Jesus Soares; Sérgio dos Santos Silva; Débora de Souza Tavares; Jeandson Silva Viana; Brenda Colleen Clifton Cardoso (International Journal of Agronomy)
Ormosia arborea is a tree species planted in urban areas and used to restore degraded areas. Its seeds are dormant and propagation is difficult. This study compares different dormancy breaking methods and physiological seed quality and seedling production. The seeds were germinated in sand in the laboratory of the Universidade Estadual de Santa Cruz, Ilhéus, Bahia, Brazil. The following dormancy breaking treatments were applied: control (intact seeds), 100°C water immersion; boiling water immersion followed by 24 hours of soaking; scarification with number 100 and number 50 sandpaper opposite from root emergence; sulfuric acid immersion for 1 hour, 50, 45, and 30 minutes. Seed immersion in 100°C and boiling water did not break the dormancy. The study species showed a greater vigor of seedling when its seeds were submitted to treatments associated with tegument rupturing by sandpaper or sulfuric acid. On the other hand, seed scarification with sulfuric acid for 1 hour, 50, 45, and 30 minutes or sandpaper favored seed germination and vigor.